Robust aperiodic-disturbance rejection in an uncertain modified repetitive-control system - Zhou, Lan; She, Jinhua; Li, Chaoyi; Pan, Changzhong (Zielona Góra: Uniwersytet Zielonogórski)
This paper concerns the problem of designing an EID-based robust output-feedback modified repetitive-control system (ROFMRCS) that provides satisfactory aperiodic-disturbance rejection performance for a class of plants with time-varying structured uncertainties. An equivalent-input-disturbance (EID) estimator is added to the ROFMRCS that estimates the influences of all types of disturbances and compensates them.
Keywords: repetitive control; equivalent input disturbance; two-dimensional system; singular-value decomposition; linear matrix inequality